THE EFFECT OF SPINNING WHEEL MEDIA ON ADOLESCENT’S KNOWLEDGE ABOUT PREMARITAL SEXUAL BEHAVIOR AT SMAN 01 BENGKULU CITY - Yusinta Damayanti; Nispi Yulyana; Ratna Dewi (STIKES Mamba'ul 'Ulum Surakarta, 2026)
Background: Sexual behavior includes any action motivated by the desire to have sexual intercourse, either with the same or opposite sex. 80% of adolescents are in a relationship, with 40% going on their first date between the ages of fifteen and seventeen (SDKI, 2017). Lack of education about sexual behavior before marriage is one of the contributing problems. Objective: To determine the effect of spinning wheel media on adolescents' knowledge about premarital sexual behavior.Research Methods: A quasi-experimental design with pre-post control two groups was used in this study. A total of 64 female students of SMA Negeri 01 Bengkulu City became the research sample. The sampling method used was proportional stratified random sampling. The research data were analyzed using Independent T-Test. Results: Adolescent knowledge about sexual behavior before marriage is influenced by spinning wheel media, as shown by the ρ value of 0.000. The results showed an increase in the average knowledge score of 26.46 points after intervention with spinning wheel media, while through disc media, there was an increase of 21.67 points. Conclusion: The use of spinning wheel media is more influential than disc media on adolescents' knowledge of premarital sexual behavior. Keywords: Premarital Sexual Behavior; Spinning Wheel; Knowledge